2022
DOI: 10.1155/2022/2218140
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Prognostic Values of CXCL Family in Epstein–Barr Virus Associated Gastric Cancer

Abstract: Background. CXCL family is a class of secreted growth factors signaling through G-protein-coupled receptors, and abnormal expression is associated with the growth and progression of many tumors. However, their prognostic value has been poorly studied in Epstein–Barr virus- (EBV-) associated gastric cancer (EBVaGC). Therefore, it is of great significance to explore the prognostic value of the CXCL family in EBVaGC. Methods. CXCL family mRNA expression was analyzed in STAD data from The Cancer Genome Atlas (TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Besides, a research of CXCL family related to Epstein-Barr virus (EBV) associated gastric cancer has elucidated that the expression differences of CXCL family members were closely related to the progression of EBV-associated GC, including the relationship with clinical stage, virus infection, prognosis, etc. It was reported that changes in CXCL9, CXCL10, CXCL11 and CXCL17 mRNA expression had potential prognostic values in patients with EBV-associated GC [ 28 ]. Moreover, Zhou et al had discovered that macrophages, which were induced by the secretion of TNF-α from GC cells released CXCL1 and CXCL5.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…Besides, a research of CXCL family related to Epstein-Barr virus (EBV) associated gastric cancer has elucidated that the expression differences of CXCL family members were closely related to the progression of EBV-associated GC, including the relationship with clinical stage, virus infection, prognosis, etc. It was reported that changes in CXCL9, CXCL10, CXCL11 and CXCL17 mRNA expression had potential prognostic values in patients with EBV-associated GC [ 28 ]. Moreover, Zhou et al had discovered that macrophages, which were induced by the secretion of TNF-α from GC cells released CXCL1 and CXCL5.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…Similarly, TNFs and interferon receptors facilitate the initiation of cell pathways associated with infections [ 31 , 32 , 33 ]. These genes were previously studied concerning HBV, HCV, liver diseases, and viral-induced cancers [ 34 , 35 , 36 ], but no study showed this gene with expression profiles in HEV infections. The expression of the seven immune response genes CCL2, CCL5, CXCL10, CXCL15, TNF, IFNGR1, and SAMSN1 was evaluated through a real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CXCL9/10/11/17 mRNA may be a promising prognostic indicator for Epstein-Barr virus associated STAD patients. [ 16 ] Another study revealed that CXCL9 was positively correlated with a better prognosis for STAD patients. [ 17 ] Moreover, combinations of initial serum ENA78/CXCL5 and SDF-1/CXCL12 can serve as serum biomarker panels to predict the presence and distant metastasis of STAD.…”
Section: Discussionmentioning
confidence: 99%